(untitled) (Journal of history-rus, 2023)
This study aimed to analyze the institutional repository of academic institutions in Kazakhstan in promoting open access with a focus on its history and development. The specific objectives of the study were to analyze the registration year of the institutional repository, the type of contents, and the subjects found in an institutional repository of each academic institution in the Open Directory of Open Access Repository. Both quantitative and qualitative approaches were employed. Webometrics and content analysis were methods used in data collection and analysis. Data was collected directly from the Directory of Open Access Repository. Microsoft Office Excel 2010 was used to analyze quantitative data. The findings of the study reveal the inconsistency of the registrations of the academic institutional repositories to the Open Directory of Open Access Repository in terms of the year. On the other hand, findings reveal the registration of only eight institutional repositories into the Open Directory of Open Access Repository among hundreds of academic institutions in Kazakhstan in which only one institutional repository among the top five rated universities was observed. Furthermore, findings indicate the dominance of journal articles as the main type of content that almost all institutional repositories added to the Open Directory of Open Access Repository. Additionally, findings show the dominance of arts, science, technology, humanities, social science, and health and medicine as the main subjects added by the majority of institutional repositories added to the Open Directory of Open Access Repository. The study concludes that when compared with findings of similar studies from foreign countries, the registration of institutional repositories of academic institutions in Kazakhstan to the Open Directory of Open Access Repository is not encouraging and therefore limits open access. The study therefore, recommends more registration of institutional repositories of academic institutions to the Open Directory of Open Access Repository particularly the top-ranked universities in order to increase the visibility of scholarly works globally and therefore increase the reputations and prestige of the universities of Kazakhstan more importantly to promote open access. Also, priority should be given to theses and dissertations to be added to the institutional repositories as they also contribute to increasing the reputations of the academic institutions.